Beirare Of Power Grabbers In Our Midst Warns PM - New Strait Times, (2008)
Power grabbers are hard at work taking advantage of the difficult conditions to fire up the people's sentiments with false promises Prime Minister Datuk Seri Abdullah Ahmad Badawi Said.